I dare you! - Brezenoff, Steven (Makato, Minnesota Stone Arch Books, [2009])
"Kayla is dared to sleep over inside a creepy house, but the next morning, she won't wake up! Her friends must figure out what happened"--Unedited summary from book
A gift from book Africa
Crim & Mystery
1 2 13 15
NEW_ZTN_GN
Keywords: Clubs -- Juvenile fiction; Detective and mystery stories; Mystery and detective stories